High-resolution vessel wall imaging after mechanical thrombectomy. Issue 6 (December 2021) - Kasab, Sami Al; Bathla, Girish; Varon, Alberto; Roa, Jorge A; Sabotin, Ryan; Raghuram, Ashrita; Chaorong, Wu; Hasan, David M; Turan, Tanya N; Chatterjee, Rano; Samaniego, Edgar A
Objectives: High-resolution magnetic resonance imaging has the potential of characterising arterial wall changes after endovascular mechanical thrombectomy. The purpose of this study is to evaluate high-resolution magnetic resonance imaging features of large intracranial arteries following mechanical thrombectomy. Methods: Patients who presented with acute ischaemic stroke due to large vessel occlusion and underwent mechanical thrombectomy were prospectively recruited. Subjects underwent high-resolution magnetic resonance imaging within 24 hours of the procedure. Magnetic resonance imaging sequences included whole brain T1 pre and post-contrast black-blood imaging, three-dimensional T2, contrast-enhanced magnetic resonance angiography and susceptibility-weighted imaging. Arterial wall enhancement was objectively assessed after normalisation with the pituitary stalk. The contrast ratio of target vessels was compared with non-affected reference vessels. Results: Twenty patients with 22 target vessels and 20 reference vessels were included in the study. Sixteen patients were treated with stentriever with or without aspiration, and four with contact aspiration only. Significantly higher arterial wall enhancement was identified on the target vessel when compared to the reference vessel (U = 22.5, P  < 0.01). The stentriever group had an 82% increase in the contrast ratio of the target vessel (x̄ = 0.75 ± 0.21) when compared to the reference vessel (x̄ = 0.41 ± 0.13), whereas the contact aspiration group had a 64% increase of the contrast ratio difference between target (x̄ = 0.62 ± 0.07) and reference vessels (x̄ = 0.38 ± 0.12). Approximately 65% of patients in the stentriever group had a positive parenchymal susceptibility-weighted imaging versus 25% in the contact aspiration group. There was no statistically significant correlation between susceptibility-weighted imaging volume and the percentage increase in the contrast ratio ( rs  = 0.098, P  = 0.748). Conclusions: This prospective pilot study used the objective quantification of arterial wall enhancement in determining arterial changes after mechanical thrombectomy. Preliminary data suggest that the use of stentrievers is associated with a higher enhancement as compared to reperfusion catheters.